Evaluasi aktivitas analgesik dan antidiare ekstrak etanol bunga telang (Clitoria ternatea Linn.) - Ananda, RA Dewinta Sukma; Kusumawardani , Nurul; Fauzi , Rizal; Estiningsih , Daru; Emelda, Emelda; Solikah , Wahyu Yuliana; Nurinda , Eva; Gunawan , Adhi; Ramandani , Wulan; Stiawati , Rika (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2024)
The analgesic and antidiarrheal effects of Clitoria ternatea Linn. flower extract were tested in mice. A significant analgesic response (p<0.05) was observed in acetic acid-induced pain models in a dose-dependent manner. The percent protection of analgesic properties was calculated from the reduction of writhing by butterfly pea ethanol extract. The Butterfly pea extract doses at 100, 200, and 400 mg/ kg showed analgesic protection by 76.6% (9.4 ± 3.65), 93.9% (2.4 ± 1.95), and 97.5% (1.0 ± 0.71), respectively. The antidiarrheal properties of Clitoria ternatea Linn. flower extract were assessed using the castor oil-induced diarrhea method. Clitoria ternatea Linn. flower extract delayed the onset of castor oil-induced diarrhea in a dose-dependent manner and reduced the frequency of defecation. There was no significant difference (p>0.05) between the effects of 400 mg/kg of Clitoria ternatea Linn. flower extract and loperamide in protecting mice against castor oil-induced diarrhea. Based on the study results, it is suggested that the Clitoria ternatea Linn. flower extract has strong analgesic and antidiarrheal properties.